2012
DOI: 10.4067/s0717-95022012000200063
|View full text |Cite
|
Sign up to set email alerts
|

Gross Anatomical, Histological and Histochemical Studies on the Postnatal Development of the Prostate Gland of Gaddi Goat

Abstract: SUMMARY:The study was conducted on the prostate gland of Gaddi goat from one day old to more than five years of age divided into three groups viz; Prepubertal (1 day old to < 18 months of age), Pubertal (18 months to < 5 yrs of age) and Postpubertal (> 5 yrs of age). The prostate comprised of corpus prostatae, a band like structure close to the junction of vesicular gland with the urethra, and the pars disseminate which extended in urethra well from its origin to the point of duct of bulbourethral gland. Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 7 publications
(4 reference statements)
7
10
0
Order By: Relevance
“…The strong activity of NSE was observed in glandular and ductular epithelium, whereas the smooth and skeletal muscles showed weak and moderate reaction, respectively (Fig 19) (Table 2). Similar findings have been reported in ram (Roy et al1985), goat (Pawar et al 1988), buffalo bull (Chopra, 1998) and Gaddi goat (Pathak et al 2012).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The strong activity of NSE was observed in glandular and ductular epithelium, whereas the smooth and skeletal muscles showed weak and moderate reaction, respectively (Fig 19) (Table 2). Similar findings have been reported in ram (Roy et al1985), goat (Pawar et al 1988), buffalo bull (Chopra, 1998) and Gaddi goat (Pathak et al 2012).…”
Section: Resultssupporting
confidence: 83%
“…Fine granular activity of LDH was found in parenchyma and weak in the stroma (Fig 9), which may be related to its role in conversion of pyruvate to lactate as it is an enzyme of glycolysis. Moderate activity of G-6-PD was observed in parenchyma and weak in the stroma (Fig 6).The glandular and the ducts of bulbourethral were strongly positive for diaphorases (NADPHD and NADHD) whereas a weak activity for NSE (Table 3) was observed (Fig 15, 18 and 20).Similar findings have been reported in ram (Roy et al1985), goat (Pawar et al 1988), buffalo bull (Chopra, 1998), buck (Pyne et al 1991) and Gaddi goat (Pathak et al 2012).…”
Section: Resultssupporting
confidence: 75%
“…The luminal border and subapical cytoplasm gave strong positive reactions for neutral mucopolysaccharides, whereas the reaction was mild in the rest of the cytoplasm in the corpus prostate of camel [16]. The cytoplasm of all the secretory end pieces was strongly PAS-reactive in Gaddi goat [13], which was in accordance with the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The Alcian blue reaction was strongly positive in certain lobules [18], as seen in summer in the present findings. In pubertal animals, the cytoplasm of all the secretory end pieces showed very strong Alcian blue reactions at the luminal border [13]. Similar to the current study, in buffalo bulls [3] and in bucks [18] researchers found mucoprotein and glycoprotein in the serous alveoli.…”
Section: Discussionsupporting
confidence: 87%
“…Fragmentary anatomical reports on the anatomy of testis of Malabari goats (Harshan et al, 1978), Assam goats (Baishya et al, 1985(Baishya et al, , 1986, Maradi (Red Sokoto) goats (Ogwuegbu et al, 1985;Nwoha, 1995), Beetal goats (Gupta, 1989), German Brown, Anglo Nubian goats and Caninde goats (Barnabe et al, 1992), Cashmere goats (Walkden-Brown et al, 1994) and Japanese Tokara goats (Nishimura et al, 2000) are available. The Gaddi goats which are the inhabitants of North Western Himalayas of India and lend a vital support to the livelihood of the local tribes have not been utilized for such study so far (Pathak et al, 2012). The present paper reports the basic anatomical data on the testes and epididymis of Gaddi goats at different ages and state of reproduction.…”
Section: Introductionmentioning
confidence: 99%